2019
DOI: 10.4046/trd.2018.0070
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Korean Patients with Lung Cancer Who Have Programmed Death-Ligand 1 Expression

Abstract: Background Programmed death-ligand 1 (PD-L1), a transmembrane protein, binds to the programmed death-1 (PD-1) receptor, and anti-PD-1 therapy enables immune responses against tumors. This study aimed to assess clinical characteristics of PD-L1 expression using immunohistochemistry among Korean patients with lung cancer. Methods We retrospectively reviewed the data of patients with pathologically proven lung cancer from a single institution. PD-L1 expression determined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The color of the chromogenic reaction is modified using a chromogen enhancement reagent; the specimen may then be counterstained and cover slipped. Results were interpreted using a light microscope [38]. All stained slides were evaluated by a board-certified pathologist for PD-L1 membrane staining.…”
Section: Methodsmentioning
confidence: 99%
“…The color of the chromogenic reaction is modified using a chromogen enhancement reagent; the specimen may then be counterstained and cover slipped. Results were interpreted using a light microscope [38]. All stained slides were evaluated by a board-certified pathologist for PD-L1 membrane staining.…”
Section: Methodsmentioning
confidence: 99%
“…The U.S. FDA approved the 22C3 antibody for pembrolizumab, the 28-8 antibody for nivolumab, and SP142 for atezolizumab [46]. Many studies have reported that PD-L1/PD-1 levels correlate to treatment response and prognosis; however, further research will be needed to fully understand these pathways in cancer [47]. Calretinin, BAP1, podoplanin, CK5, CK5/6, and WT1 can be potentially used for the diagnosis of mesothelioma [48].…”
Section: Ihc Testsmentioning
confidence: 99%
“…Therefore, studies are ongoing to identify additional predictive tumor-based markers for ICI response, such as tumor-infiltrating lymphocytes, microsatellite instability (MSI), mismatchrepair deficiency, and tumor mutational burden (TMB) (10). However, PD-L1 expression on the tumor cell is the only biomarker for ICI response used in routine practice (11), and other potential candidates are not currently clinically relevant.…”
Section: Introductionmentioning
confidence: 99%